Determinants of Financial Distress and Its Implications on Corporate Value Case Study on Property and Real Estate Sub-Sector Stocks on the Indonesia Stock Exchange Pandemic Era - Dini Hadiati Putri Kinasih; Luqman Hakim; Riyanti Riyanti (Greenation Research & Yayasan Global Resarch National, 2023)
The purpose of this study is to determine and analyze the effect of profitability (ROA), liquidity (CR), financial leverage (DER), and SIZE on company value with financial distress as an intervening variable in property and real estate sub-sector companies in the pandemic era. The test conducted in this study is path analysis, with a sample number of companies of 51 and 3 years of research. This study's results show a significant influence between ROA, CR, DER, and SIZE on financial distress. And there is a significant direct influence between ROA, CR, and SIZE on company value. However, DER has a direct but insignificant effect on the company's value. Financial distress can mediate the relationship between Return on Assets, Current Ratio, and company size to company value but does not mediate the relationship of Debt to Equity Ratio to company value.